2022
DOI: 10.7324/japs.2023.59304
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based screening of inhibitor platelet-derived growth factor from ethanol extract of Uncaria gambir (Hunter) Roxb. as an antifibrotic in keloid fibroblast cells

Abstract: This study aimed to determine the potency of the compounds in gambir [Uncaria gambir (Hunter) Roxb.] to inhibit the proliferation of keloid fibroblasts using an in silico study with molecular docking and an in vitro assay. In this study, the interaction between compounds found in the gambir plant and platelet-derived growth factor subunit A (PDGF-α) as the target protein and the percentage inhibition were analyzed to determine its potential as a candidate for herbalbased keloid therapy. The compounds found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A total 74 bioactive compounds of Uncaria gambir (Hunter) Roxb. were identified from the literature study [ 9 , 17 , 24 ], with 5048 protein-specific targets based on SWISS target prediction. A total of 277 targets from 29 bioactive compounds were predicted to be targeted to keloid-related target proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total 74 bioactive compounds of Uncaria gambir (Hunter) Roxb. were identified from the literature study [ 9 , 17 , 24 ], with 5048 protein-specific targets based on SWISS target prediction. A total of 277 targets from 29 bioactive compounds were predicted to be targeted to keloid-related target proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Keloid is defined as tissue fibrosis due to its effusive accumulation of ECM, particularly collagen [ 2 ]. Jusman et al [ 17 ] have shown that some gambir bioactive compounds have potency to inhibit platelet-derived growth factor subunit A (PDGFA) as a target protein to reduce fibroblast proliferation through in silico study. Therefore, gambir is assumed to be a promising herb-based antifibrotic agent to deal with keloid disease.…”
Section: Introductionmentioning
confidence: 99%